2007
DOI: 10.1016/j.cor.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the benefits of remanufacturing option under one-way substitution and capacity constraint

Abstract: In this article, we investigate the profitability of remanufacturing option when the manufactured and remanufactured products are segmented to different markets and the production capacity is finite. A single period profit model under substitution is constructed to investigate the system conditions under which remanufacturing is profitable. We present analytical findings and computational results to show profitability of remanufacturing option under substitution policy subject to a capacity constraint of the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…They consider continuous review (S-1, S) inventory control policy for both types of products. Bayindir et al (2007) extend these two studies by considering a finite production capacity. Yongjian et al (2006) consider the problem with multiple product types and multiple periods and develop a DP-based approximate solution procedure to obtain near optimal solutions.…”
Section: Inventory Substitutionmentioning
confidence: 97%
“…They consider continuous review (S-1, S) inventory control policy for both types of products. Bayindir et al (2007) extend these two studies by considering a finite production capacity. Yongjian et al (2006) consider the problem with multiple product types and multiple periods and develop a DP-based approximate solution procedure to obtain near optimal solutions.…”
Section: Inventory Substitutionmentioning
confidence: 97%
“…Dobos and Richter [14] studied the quality of used products in an integrated production recycling system, and showed that it is better for the manufacturer to only buy back reusable products. Also, many applications and methods for analyzing the hybrid manufacturing system are discussed in [5][6][7]60,1,41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that offering substitution leads to lower levels of recovered inventory. Single-period problems with two-way substitution have been studied by Bayindir et al [11] and Kaya [12], who assume that the proportion of customers who accept a substitution is known and constant. The quality of returned used goods is addressed by Kaya [12] by way of an incentive paid to the consumer in exchange for returning used goods.…”
Section: Introductionmentioning
confidence: 99%